2015
DOI: 10.1021/ja5130379
|View full text |Cite
|
Sign up to set email alerts
|

Triggered Exchange of Anionic for Neutral Guests inside a Cationic Coordination Cage

Abstract: Molecular encapsulation processes under the control of an external trigger play a major role in biological signal transduction processes and enzyme catalysis. Here, we present an artificial mimic of a controllable host system that forms via self-assembly from a simple bis-monodentate ligand and Pd(II) cations. The resulting interpenetrated double cage features three consecutive pockets which initially contain one tetrafluoroborate anion, each. Activation of this host system with two halide anions triggers a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(102 citation statements)
references
References 67 publications
3
96
0
2
Order By: Relevance
“…Lö ffler et al 66 have recently reported the synthesis of the interpenetrated double palladium cage 136 (Scheme 2). The double cage contains a stack of four palladium ions each bridged by a tetrafluoroborate anion.…”
Section: Self-assembling Systems Involving Anionsmentioning
confidence: 99%
“…Lö ffler et al 66 have recently reported the synthesis of the interpenetrated double palladium cage 136 (Scheme 2). The double cage contains a stack of four palladium ions each bridged by a tetrafluoroborate anion.…”
Section: Self-assembling Systems Involving Anionsmentioning
confidence: 99%
“…[3] The obtained structure was optimized on ωB97XD/def2-SVP DFT level (charge: +5, multiplicity: singlet, with three BF 4 − inside the three internal pockets, no constraints) using the dispersion-corrected ωB97XD functional implemented in Gaussian '09 [4] and the Ahlrich def2-SVP basis set obtained from the EMSL basis set exchange website https://bse.pnl.gov/bse/portal. [5] Hydrogen atoms are omitted for clarity.…”
mentioning
confidence: 99%
“…Varying the guest anions can force the double cages into binding less favorable secondary guests. Small halides are favored in the terminal cavities, which forces the central Pd II ions closer to each other, creating a larger internal cavity that is capable of binding neutral species such as benzene or norbornane in an allosteric manner . As well as simple lone pairs, the other obvious small function to internalize is a hydrogen bond donor group such as a urea, alcohol or the like.…”
Section: Structural Control In the Assembly Of Endohedrally Functionamentioning
confidence: 99%
“… Selective anion recognition in functionalized cage complexes . Adapted with permission from reference 25, copyright 2017 American Chemical Society.…”
Section: Structural Control In the Assembly Of Endohedrally Functionamentioning
confidence: 99%